2016
DOI: 10.6018/red/49/7
|View full text |Cite
|
Sign up to set email alerts
|

Sistema de formación continua para la alfabetización digital de los docentes de la escuela de hotelería y turismo de Cienfuegos

Abstract: ResumenA partir de las trasformaciones que las TIC han provocado en todas las esferas de la sociedad, se le ha atribuido gran importancia a la alfabetización digital de los docentes de las escuelas de hotelería y turismo, tanto internacionalmente como en nuestro territorio. Sin embargo, esta formación, no se ha abordado de manera reiterada y sistémica, o sea, se han planificado cursos y entrenamientos, pero aislados y desconectados, además, sin tener en cuenta posibilidades de desarrollo como el aprendizaje co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…This contradicts previous research that found specialization as a characteristic feature of research on literacy, and specifically on DL [9,[30][31][32]. To the results obtained in the SCOPUS database, it is necessary to add other investigations located in other databases that have served to build the theoretical framework and that contrast with the results presented because they focus on tourism, on teachers and are largely signed by the same authors [37][38][39].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This contradicts previous research that found specialization as a characteristic feature of research on literacy, and specifically on DL [9,[30][31][32]. To the results obtained in the SCOPUS database, it is necessary to add other investigations located in other databases that have served to build the theoretical framework and that contrast with the results presented because they focus on tourism, on teachers and are largely signed by the same authors [37][38][39].…”
Section: Discussionmentioning
confidence: 79%
“…From the above, it is understood that notable interest exists in academic research on the literacy of university students [1,19,31] characterized by a constant adaptation to the new demands derived from the changes experienced by the social environment, which are caused, to a large extent, by technological development [10,16,19,32]. Another feature that defines research on literacy, and specifically on DL, is its focus or specialization in specific areas or disciplines in response to the different levels of demand that professional sectors require of graduates [9,[33][34][35], including the tourist field [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La competencia mediática es un fenómeno comunicativo que combina conocimientos, destrezas y actitudes (Ferrés y Piscitelli, 2012) para acceder a los medios (Borges et al, 2020) de forma crítica (Alfonzo, 2020). Es decir, comprenderlos, evaluarlos y crear comunicaciones (Aguaded y Pérez, 2012) o recursos mediáticos (Avello- Martínez et al, 2013) mediante diversos tipos de lenguajes, tecnologías o formas simbólicas que colaboren con nuevos conocimientos (Alfonzo, 2020) o fomenten el pensamiento crítico (Ríos et al, 2022).…”
Section: Conceptualizando La Competencia Mediáticaunclassified
“…Según Avello et al (2016) el ritmo acelerado de la llegada e imposición de las tecnologías digitales en las áreas educativas es un desafío para los profesores porque es superior a la capacidad de adaptación de estos. Observando este punto se encuentra que cuando los maestros apenas están logrando adaptarse a una tecnología, simultáneamente ya están en desarrollo otras herramientas que se introducen de forma prácticamente inmediata en el ejercicio educativo .…”
Section: Procedimientounclassified